2015
DOI: 10.1016/j.jastp.2015.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Winter-time dependence of the global TEC on the stratospheric temperature and solar radiation

Abstract: Cite this article as: Plamen Mukhtarov and Dora Pancheva, Winter-time dependence of the global TEC on the stratospheric temperature and solar radiation, Journal of Atmospheric and Solar-Terrestrial Physics, http://dx.Abstract: This paper presents a simple linear regression model that enables to quantify the contribution of high-latitude stratospheric temperature and solar radiation (describes by its proxy F10.7) to the variability of the low-latitude TEC during winter. The model is based on cross-correlation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Stratospheric warming also begins on the same date. According to the study of the response of zonal mean TEC to stratospheric warming, a negative response is observed that increases towards tropical latitudes [18,21]. In this particular case, relative TEC decreases and becomes negative at low latitudes under both stratospheric warming and the decrease in F10.7 after 11 February.…”
Section: Stratospheric Warming and Solar And Geomagnetic Influences O...mentioning
confidence: 99%
See 1 more Smart Citation
“…Stratospheric warming also begins on the same date. According to the study of the response of zonal mean TEC to stratospheric warming, a negative response is observed that increases towards tropical latitudes [18,21]. In this particular case, relative TEC decreases and becomes negative at low latitudes under both stratospheric warming and the decrease in F10.7 after 11 February.…”
Section: Stratospheric Warming and Solar And Geomagnetic Influences O...mentioning
confidence: 99%
“…These studies show that the influence of SSW on the ionospheric electron density occurs through the so-called "disturbed dynamo", a change in the wind system in the lower thermosphere and, as a consequence, anomalies in the electric fields that shape the EIA. In one paper [21], through a statistical analysis of the period 2005-2010 using TEC data under winter conditions, it was found that variations in stratospheric temperature at 60 • N latitude affect the TEC regardless of whether SSW occurs. In [22], a situation was simulated in which the October 2003 Halloween storm coincided in time with a major SSW.…”
Section: Introductionmentioning
confidence: 99%
“…The results of recent studies show convincingly that the sources in lower atmospheric layers (troposphere and stratosphere) can have a considerable effect on the ionospheric plasma condition (Kazimirovsky, ; Lastovicka, ; Yiğit et al, ). For example, equatorial ionosphere variability related to low atmosphere temperature changes is shown to be up to a half of the solar‐induced one (Mukhtarov & Pancheva, ). The above stimulates a growing interest in the atmospheric‐ionospheric coupling research.…”
Section: Introductionmentioning
confidence: 99%